The Impact of Reclamation on Tidal Flat Morphological Equilibrium - Zhong, Zehua; Hu, Zhan (Frontiers in Marine Science, 2021)
Reclamation is one of the most prominent anthropogenic activities affecting tidal flat morphology and the related ecosystem service. Two representative types of reclamation are upper-flat enclosure and lower-flat enrockment. From a historical perspective, different type of reclamation was adapted in different areas in ancient China. As previous studies on reclamation are often site-specific, the reason that leads to such a difference is unclear. The intertidal dynamic equilibrium theory (DET) provides a comprehensive framework for this quest. Here, we extend the DET with additional effects of reclamation. A model based on DET (DET-ESTMORF) was applied to investigate the impact of reclamation on tidal flats. The model was validated by comparing our results against previous records and observations. Results show that both types of reclamation induce morphological adjustment by enhancing local accretion, which upset the previous equilibrium. Specifically, upper-flat enclosure drives tidal flats into evolution toward wave dominance, whereas lower-flat enrockment causes adjustment toward tidal dominance. Next, the impact of reclamation on tidal flats in different states (prograding or retreating) was investigated. We show that both enclosure and enrockment can induce accretion despite the varying wave climate and sediment supply, with the mean accretion rate raised by 1.8 cm/year and 1.2 cm/year, respectively. However, the resulting profiles are different in shape, especially on retreating flats. Finally, we point out that tidal range and sediment supply are the potential reasons affecting the choice of reclamation types in practices.